"A concentration of private power without equal in history": Economic concentration and the investigations of the Temporary National Economic Committee (1938-41) - William VanLear; Daniel Hutchinson (Levy Economics Institute of Bard College, 2025)
This manuscript presents a detailed summary and reassessment of the 1941 final report of the Temporary National Economic Committee (TNEC). We portion the manuscript into four major parts: background, major themes, assessment of the report, and additional analysis and reflection. In the first section, we cover what compelled the government's investigation and we identify the committee's makeup and mission. We also identify eight historical precedents for the report. In the major themes section, we provide a detailed layout of the TNEC's "monopoly investigation" and its search for what structural impediments may have existed to economic recovery during the 1930s. The themes include competition, concentration, technology, trade barriers, business investment, small business, and fiscal and monetary policy. Part 3 assesses the report by looking at one important early assessment completed in the 1940s. We identify three TNEC concerns, namely the (1) development of oligopoly, (2) savings-investment imbalance, and (3) war mobilization and democracy. Part 3 understands the TNEC report from an institutionalist or stage theory perspective of history and economics. This part ends with a review of conservative thinking at the time of the report and shortly thereafter. The final section looks at the connection between the institutional context of the economy and the economy's economic performance. It is clear that the TNEC understood that systemic economic change had occurred since the Gilded Age, and that the economy had become oligopolized well before the Great Depression. The committee came to believe that the evolution of the economic system into a concentrated corporate one had increased inequality, the effect of which was to boost the volume of savings while retarding the level of investment.
Keywords: 330; Government Report; Economic Concentration; Structural Impediments; Political Economy